Adjustable Compliance Joint with Torsion Spring for Human Centred Robots - Dimitar Chakarov; Mihail Tsveov; Ivanka Veneva; Peter Mitrouchev (International Journal of Advanced Robotic Systems, 2015)
Human-oriented robots should be human-friendly, safe and impact-free. The present work is about the problem of adjustable compliance implementation in human-friendly robots. A new passive compliance adjustable compliant joint based on a variable length leaf torsion spring is presented. It allows a wide range of independent positioning and stiffness regulation. Some characteristics of the leaf torsion spring are analysed: stiffness\compliance, torque, elastic deformation angle and generated potential energy. Numerical simulations are performed. The structural parameters' influence on the compliant joint's characteristics is estimated. Tests on a specially realized prototype of an adjustable compliant joint are carried out. The basic prototype characteristics are evaluated. The experiments show a very good correlation with the numerical simulations.